A Histoarchitectural Approach to Skeletal Muscle Injury: Searching for a Common Nomenclature. Issue 3 (17th March 2020) - ,; Balius, Ramon; Blasi, Marc; Pedret, Carles; Alomar, Xavier; Peña-Amaro, José; Vega, José A.; Pruna, Ricard; Ardèvol, Jordi; Álvarez, Guillermo; de la Fuente, Javier; Fernández-Jaén, Tomás; et al.
In recent years, different classifications for muscle injuries have been proposed based on the topographic location of the injury within the bone-tendon-muscle chain. We hereby propose that in addition to the topographic classification of muscle injuries, a histoarchitectonic (description of the damage to connective tissue structures) definition of the injury be included within the nomenclature. Thus, the nomenclature should focus not only on the macroscopic anatomy but also on the histoarchitectonic features of the injury.